Effect of the food and nutrition program on the recovery of people with extreme poverty affected by tuberculosis; Tacna Province, 2013 - Calderón Fernández, Victoria (2017)
Program in the recovery of people affected extreme poverty of tuberculosis in the province of Tacna in 2013. Design explanatory cross-sectional study. Materials and Methods: 467 medical records of patients admitted a treatment for tuberculosis were reviewed, finding 33 people in poorness extreme, obtaining information from their social condition, disease, and whoare interviewed about the pattern of consumption food basket of PANTBC. For the analysis took into account the socio-economic characteristics, disease progression, remission of symptoms, nutritional assessment according to the Body Mass Index (BMI) at the beginning and end of treatment. Results: All patients entered the program with sensitive tuberculosis diagnosis and treatment at the end of his condition was cured. In 90.9%he referred the symptoms, with favorable clinical and bacteriological assessment. Of the total patients admitted underweight 70% culminated with normal weight.